Asupan yodium dan asupan goitrogenik hubungannya dengan status gangguan akibat kekurangan yodium (GAKY) pada anak sekolah dasar di Kabupaten Dairi Provinsi Sumatera Utara - Urbanus Sitohang; Toto Sudargo; Dhuto Widagdo (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2008)
Background: Iodine deficiency disorder (IDD) is a health problem which affects the quality of human resources. IDD is caused by lack of iodine substance. The substance is needed for numerous syntheses and metabolism in the body, particularly thyroid glands. IDD may also be caused by high consumption goitrogenic substance.Objective: The study was meant to identify relationship between iodine and thiocyanate intake and IDD, and to identify differences in iodine and thiocyanate intake based on endemic level.Method: This was an observational study with cross sectional design. Method used were palpation of goiter glands to measure endemic level, food recall, and food frequency questionnaire (FFQ) to measure iodine and thiocyanate intake, ammonium persulfate digestion to measure urine iodine excretion. Data analysis used chi-square, Pearson correlation and anova.Results: The result of chi-square analysis showed that there was no significant relationship between iodine intake and IDD (p > 0.05, CI 95%: 0,34–1,18), but there was significant relationship between iodine intake and urine iodine excretion (p < 0.05, CI 95%: 2.2–7.2) with OR 3.9. There was significant relationship between IDD and thiocyanate intake (p < 0.05, CI 95%: 3.0–11.3) with OR 5.9, but there was no significant relationship between thiocyanate intake and urine iodine excretion (p > 0.05, CI 95%: 0.48–1.97). The result of Pearson correlation test showed that there was no significant relationship between iodine and thiocyanate FFQ and IDD (p > 0.05); there was no significant relationship (but there was a tendency) between thiocyanate FFQ and IDD (p > 0.05). There were significant differences in iodine intake, thiocyanate intake, iodine FFQ and thiocyanate FFQ based on endemic level (p > 0.05).Conclusion: There was relationship between iodine intake and IDD/non-IDD, but there was relationship between urine iodine excretion and IDD. Children with IDD had higher consumption of thiocyanate than those who did not have IDD. There were differences in all measurements based on endemic level.